Gap Pengaruh Pelayanan Informasi Obat terhadap Kepuasan Pasien Rawat Jalan di Instalasi Farmasi Rumah Sakit YARSI Pontianak - Iska Lestari, Maulidia; Marwiyati Rohmana, Vivin; Puteri Santika, Aprilia (Journal of Innovative and Creativity, 2026)
Drug information services re an essential component of hospital pharmaceutical care aimed at improving patients’ understanding of the proper, safe, and rational use of medications. Service quality that does not meet patient expectations may create a gap between perceived and expected services, which can influence patient satisfaction. This study aimed to analyze the gap between the drug information services received and the expectations of patients, as well as to determine the effect of drug information service quality on outpatient satisfaction at the Pharmacy Installation of Yarsi Hospital Pontianak. This research employed an observational study with a quantitative cross-sectional design. A total of 100 outpatients were selected using purposive sampling based on predetermined inclusion criteria. Data were collected using a validated and reliable questionnaire. Data analysis included normality testing, non-parametric correlation analysis (Spearman Rank), and gap analysis to measure the difference between patients’ perceptions and expectations. The service dimensions analyzed were type of drug information, pharmacists’ attitude, pharmacists’ performance, duration of drug information service, and pharmacists’ communication skills. The results showed that the overall level of patient satisfaction was categorized as very high (≥98%). The gap values for each dimension were as follows: type of drug information (-0.06), pharmacists’ attitude (-0.02), pharmacists’ performance (+0.02), duration of drug information service (-0.21), and pharmacists’ communication skills (-0.23). Statistically, the quality of drug information services did not have a significant effect on patient satisfaction, either partially or simultaneously. Overall, there was no significant difference between the perceived services and the expected services among outpatients.